Examining The Role Of Leadership In Improving Transparency And Accountability In Local Government - Syafaruddin Syafaruddin (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to evaluate the role of leadership in enhancing transparency and accountability in local government. The research will analyze how effective leadership styles and governance practices can contribute to improved decision-making transparency and public accountability at the local government level. The study will employ a qualitative approach, conducting in-depth interviews with local government leaders and employees, as well as analyzing relevant policy documents. The research findings are expected to provide valuable insights into leadership strategies that can foster a stronger culture of transparency and accountability within local government organizations. The results of this study can assist local governments in developing better governance practices and enhancing public trust.